School-age prework experiences of young people with a history of specific language impairment - Durkin, K.; Fraser, J.; Conti-Ramsden, Gina (Sage Publications, Inc., 2012)
Young people with specific language impairment (SLI) are at risk for poorer outcomes with respect to employment in adulthood, yet little is known of how early school-age prework experiences prepare them for the job market. This study examined whether young people with SLI engage in similar types of early work experiences as their typically developing (TD) peers. A total of 139 young people with a history of SLI and 124 TD peers attending their final year of compulsory secondary education were interviewed about early work experiences, current part-time employment, career aspirations, and perceived workplace challenges. Individuals with SLI experienced different types of work placements and were more likely to aspire to manual tasks, whereas their TD peers aspired to professional roles. Differences in early prework experiences and vocational aspirations are already evident in 16-year-old young people with SLI. Several challenges and potential barriers to employment are identified.